2005
DOI: 10.1007/s10157-004-0326-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bleeding complications in percutaneous renal biopsy

Abstract: For those who are clinically suspected of having amyloidosis or hypertension, more careful biopsy procedures and observations are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
151
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 15 publications
8
151
2
1
Order By: Relevance
“…This is comparable to previous work, where major hemorrhagic complication rates after native renal biopsies were reported as ranging from 1 to 8% (15,(17)(18)(19)(20)(21). This study included 148 patients with a known monoclonal gammopathy.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This is comparable to previous work, where major hemorrhagic complication rates after native renal biopsies were reported as ranging from 1 to 8% (15,(17)(18)(19)(20)(21). This study included 148 patients with a known monoclonal gammopathy.…”
Section: Discussionsupporting
confidence: 83%
“…A few studies have analyzed the bleeding risk associated specifically with amyloidosis. Eiro et al (20) found a higher rate of bleeding (defined as drop in hemoglobin by Ͼ1 g/dl) in patients with amyloidosis compared with other histologic findings, although this considered just four patients with the diagnosis. Conversely, Soares et al (15) found 4% of 101 patients with amyloidosis developed a major hemorrhagic complication; this was not significantly greater than the control group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Generally, in pregnant women with new onset of hypertension, aggressive blood pressure reduction could be harmful for the fetus and a reasonable goal is recommended to be systolic pressure between 140 and 160 mmHg and diastolic pressure between 90 and 100 mmHg by Japan Society for the Study of hypertension in pregnancy. On the other hand, increased blood pressure (systolic pressure [140 mmHg or diastolic pressure [90 mmHg) was an independent predictor of post-biopsy bleeding complications [21]. Therefore, we considered this patient at higher risk for biopsy-related bleeding.…”
Section: Discussionmentioning
confidence: 99%